National health objectives for the year 2000: the demographic impact of health promotion and disease prevention. - Stoto, M A (1991)
BACKGROUND. The national objectives in Healthy People 2000, drafted by health professionals aware of currently available public health interventions, represent a wealth of information about near-term future mortality and morbidity. METHODS. Life table methods were used to calculate the impact of projected changes in mortality and activity limitation rates on life expectancy and expected disability years. RESULTS. Meeting the mortality objectives would increase life expectancy at birth by 1.5 to 2.1 years, raising life expectancy to 76.6 to 77.2 years. In addition, meeting the target for disability from chronic conditions would increase the number of years of life without activity limitations from 66.8 years to 69.3-69.7 years. If the targets for coronary heart disease and unintentional injury were changed to reflect recent trends, a greater improvement in life expectancy at birth would be achieved: from 1.8 to 2.7 years to 76.9 to 77.8 years. CONCLUSION. Meeting the targets would have an important demographic impact. Including changes in the coronary heart disease and injuries targets, life expectancy in the year 2000 would be above the middle of the ranges used in current Census Bureau projections.